Relationships among microbiota, gastric cancer, and immunotherapy - Li, Yuzhen; Huang, Xiaona; Tong, Desheng; Jiang, Chenyu; Zhu, Xiaodan; Wei, Zhipeng; Gong, Tingjie; Jin, Chunhui (Frontiers in Microbiology, 2022)
Gastric cancer (GC) remains a major global health problem. Most of GC cases, once confirmed, have already entered an advanced stage. Currently, conventional neoadjuvant therapy or postoperative adjuvant therapy, such as chemotherapy and radiation therapy, can only bring limited survival benefits. Median survival after palliative chemotherapy is also low, at about 8-10 months. With the development of biologics,immunotargeting has become a new option for the treatment of GC, but not been widely replicated. The highly immunosuppressed tumor microenvironment (TME) is considered as the main reason discounting the efficacy of immunotherapy for GC. Therefore, new strategies are needed to enhance the immune response of the TME. In this paper, the relationship between microorganisms and GC,potential links between microorganisms and immunotherapy and some researches of microorganisms combined immunotherapy were reviewed.